1995
DOI: 10.1121/1.412080
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion of elastic waves in random particulate composites

Abstract: Elastic wave propagation in a discrete random medium is studied to predict dynamic effective properties of composite materials containing spherical inclusions. A self-consistent method is proposed which is analogous to the well-known coherent potential approximation in alloy physics. Three conditions are derived that should be satisfied by two effective elastic moduli and effective density. The derived self-consistency conditions have the physical meaning that the scattering of a coherent wave by the constitue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0
11

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 0 publications
1
43
0
11
Order By: Relevance
“…A quasistatic version for predicting mechanical properties of composites has been proposed by Berryman [1979;1980]. A dynamic generalization of this theory has been made for two and three-dimensional problems [Kim et al 1995;Kim 1996]. As shown in [Kim et al 1995], this theory was very successful in predicting the effective wave speed and attenuation in random particulate composites for wide ranges of frequency and volume fraction.…”
Section: Jin-yeon Kimmentioning
confidence: 99%
See 2 more Smart Citations
“…A quasistatic version for predicting mechanical properties of composites has been proposed by Berryman [1979;1980]. A dynamic generalization of this theory has been made for two and three-dimensional problems [Kim et al 1995;Kim 1996]. As shown in [Kim et al 1995], this theory was very successful in predicting the effective wave speed and attenuation in random particulate composites for wide ranges of frequency and volume fraction.…”
Section: Jin-yeon Kimmentioning
confidence: 99%
“…A dynamic generalization of this theory has been made for two and three-dimensional problems [Kim et al 1995;Kim 1996]. As shown in [Kim et al 1995], this theory was very successful in predicting the effective wave speed and attenuation in random particulate composites for wide ranges of frequency and volume fraction. A second variant is the dynamic extension [Sabina and Willis 1988;Bussink et al 1995;Kanaun and Levin 2003;Kanaun et al 2004] of the static self-consistent theories of [Budiansky 1965;Hill 1965].…”
Section: Jin-yeon Kimmentioning
confidence: 99%
See 1 more Smart Citation
“…Sabina and Willis demonstrated that the obtained self-consistency generate acceptable answers to determine effective dynamic properties just when wavelength of the elastic waves is at least four times that of radius of spherical inclusions. Kim et al (1995) presented an estimation of the effective dynamic properties and effective density which is similar to the coherent potential approximation in alloy physics. The obtained theoretical results are closer to the Kinra's experimental results as compared to Ying & Truell (1956) results.…”
Section: Introductionmentioning
confidence: 99%
“…A thin layer with different elastic properties is considered as the interface of matrix and inclusion in this study. Kim et al (1995) presented an estimation of effective dynamic properties and effective density via a self-consistent method which is similar to the coherent potential approximation in alloy physics. These theoretical results have a better coincidence with the experimental observations of Kinra compared to Ying & Truell results.…”
Section: Introductionmentioning
confidence: 99%